Grazing disturbance significantly decreased soil organic carbon contents of alpine grasslands on the Tibetan Plateau - Yang, Hua; Zhang, Yonggang; Li, Wei; Xu, Qingmin; Zhou, Huakun; Du, Yangong (Frontiers in Environmental Science, 2023)
Ecological security barriers on the Tibetan Plateau are threatened by climate change and human activities, such as grassland degradation and reduction of carbon fixation capacity. Understanding the influence of grazing on soil organic carbon (SOC) content and its regulating factors is important for improving the ecological barrier function of alpine grasslands. In this meta-analysis, we analysed the effects of grazing on SOC. The results indicate that grazing disturbance significantly reduced the SOC content by 13.93%, with an effect size of −0.15 ± 0.04 (p < 0.001). The effect of light grazing was not significant. The reduction range gradually increased with increasing grazing intensity. The effect of grazing activity on SOC content was driven mainly by pH and total nitrogen through a structural equation model. Future nitrogen deposition scenarios would significantly increase alpine meadow SOC on the Tibetan Plateau.